ANALISIS KREATININ DENGAN CARA EKSTRAKSI PASANGAN ION MENGGUNAKAN TRIOKTIL METIL AMMONIUM KLORIDA - , YULITA ANGELINA, Dr. Dwi Siswanta, M. Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A new creatinine analysis method with ion pair extraction using trioctyl methyl ammonium chloride (TOMA-Cl) has been studied. The optimum condition for picric-creatinine complex extraction were studied, including time, concentration of picrid acid and the mass of TOMA-Cl that used. Liniarity test, sensitivity test, and also application of extraction method has been conducted in order to determine sensitivity of the extraction method. This extraction method that was conducted is based on Jaffe method. Solution of picrid acid reacted with creatinin in base condition for an hour, then complex of picric-creatinin is extracted into cloroform using TOMA. Product of extraction is measured by UV-Vis spectrofotometer in 400-600 nm. The result showed that optimum condition of extraction method was using 150 ppm of picrid acid, 30 mg of TOMA, and range of creatinine concentration around 0-90 ppm in an hour of extraction time. Picric-creatinine complex that bind to TOMA could be extracted into cloroform solution, but the colour of complex was faded rapidly. This extraction method has good enough sensitivity.